Kekerasan dalam Rumah Tangga: Konsekuensi Hukum dan Perlindungan Korban - Yusuf Gunawan (Universitas Batanghari Jambi, 2023)
Recently, TV stations and social media were enlivened by news about domestic violence (KDRT) committed by artist FI against his wife who is also an artist named VM in a hotel in East Java. Previously, domestic violence among fellow LK artists was also horrified who experienced violence perpetrated by RB and this case ended with recovery and revocation of the police report. On social media, the viral video of domestic violence experienced by a child from his father, a businessman named RIS, has been determined as an allegation of a report from his wife after the examination and case title. Domestic violence against children which shocked the Indonesian public occurred in 1984 which was experienced by 7-year-old AH who died after being abused by his own biological father and mother. The South Jakarta District Court found Saya guilty and was sentenced to 5 years in prison while his wife S was sentenced to 3 years in prison. This research method uses a type of normative legal research that is carried out or focuses on positive legal norms in the form of laws and regulations with an empirical juridical approach by reviewing normative or juridical concepts regarding the implementation of legal protection for victims of domestic violence (KDRT) who are victims of crime. The conclusion of this study is that the reasons for the occurrence of acts of physical violence within the household (KDRT) by husbands against wives and/or children: infidelity factors, economic factors, psychological factors and the nature of the husband, educational factors, third party factors (family) and legal consequences due to acts of physical violence within the household (KDRT) by husbands against wives and/or children can be carried out through non-litigation through P2TP2A and Komnas Perempuan while handling litigation through police reporting.